EPIQ (Emotionally Immature Parents Questionnare): Pengembangan Psikometri Alat Ukur Assesing Emotionally Immature Parents - Nisa, Isnah Royhan; Islam, Azizah Fajar (Universitas Airlangga, 2025)
Parental emotional maturity significantly influences the emotional development of children. However, tools that specifically assess parental emotional immaturity are still limited. This study developed and tested the Emotionally Immature Parents Questionnaire (EPIQ), based on children's perceptions and experiences of emotionally immature parental behaviors. The questionnaire consists of 36 items, covering two main dimensions: perception and experience and five subdimensions derived from emotional maturity aspects. Data were collected from 101 participants aged 18–30 and analyzed using known group validity, construct validity, and reliability. Results showed significant group differences, adequate construct validity through confirmatory factor analysis, and high internal consistency (a = 0.963). These findings indicated that EPIQ was a reliable and valid tool for assessing parental emotional immaturity from the child’s perspective and offers valuable insights for psychological assessment and parenting intervention.